Re-creating the hybrid text: postcolonial Indian writings and the European scene - Snell-Hornby, Mary (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
For a language with a wealth of great literature such as English, globaliza-tion has been a mixed blessing. The International English of Mc World is a poor descendant of the language of Shakespeare and Dickens. On the other hand, English literature has been tremendously enriched by writings from the former colonies of the British Empire, creating their own ‘norms’ of English – ‘a new English’, as Chinua Achebe famously put it, “still in full communion with its ancestral home, but altered to suit its new surroundings ”. In the postcolonial literary scene, such ‘hybrid’ texts – or ‘métissés ’– are now a familiar feature, but a complicated one for translators working into other European languages. This essay concentrates on India, and looking at writings by Sethu (Pandavapuram in English translation) and Arundhati Roy (The God of Small Things in English and in German translation), it investigates the striking features of hybrid source texts and the cultural and linguistic problems involved in re-creating them for a European target culture.